Vertical Interfacial Engineering in Two-Step-Processed Perovskite Films Enabled by Dual-Interface Modification for High-Efficiency p-i-n Solar Cells - Zhou, Wenhao; Liu, Heng; Li, Haiyan; Zhang, Weihai; Li, Hui; Zhou, Xia; Chen, Rouxi; Zhang, Wenjun; Shi, Tingting; Abate, Antonio; Wang, Hsing‑Lin (Nano-Micro Letters, 2026)
Two-step-processed (TSP) inverted p-i-n perovskite solar cells (PSCs) have demonstrated significant promise in tandem applications. However, the power conversion efficiency (PCE) of TSP p-i-n PSCs rarely exceeds 24%. Here, we demonstrate that TSP perovskite films exhibit a vertically gradient distribution of residual PbI2 clusters, which form Schottky heterojunctions with the perovskite, leading to substantial interfacial energy-level mismatches within NiOx-based TSP p-i-n PSCs. These limitations were effectively addressed via a vertical interfacial engineering enabled by dual-interface modification incorporating tin trifluoromethanesulfonate (Sn(OTF)2) and 4-Fluorophenylethylamine chloride (F-PEA) at the NiOx/perovskite and perovskite/C60 interfaces, respectively. The functional Sn(OTF)2 not only enhances the conductivity of NiOx films but also suppresses ion migration, while inducing the formation of a Pb-Sn mixed perovskite interlayer that precisely regulates the energy level at the NiOx/perovskite interface. Complementally, F-PEA post-treatment effectively converts surface residual PbI2 clusters into a 2D perovskite capping layer, which simultaneously passivates surface defects and enhances energy-level alignment at the perovskite/C60 interface. Consequently, the optimized NiOx-based TSP p-i-n PSCs achieve a notable PCE of 25.6% with superior operational stability. This study elucidates the underlying mechanisms limiting the efficiency of TSP p-i-n PSCs, while establishing design principles for these devices targeting 26% efficiency. Highlights: 1 A vertical interfacial engineering strategy via dual-interface modification (Sn(OTF)2 at NiOx/perovskite, 4-Fluorophenylethylamine chloride (F-PEA) at perovskite/C60) solves energy-level mismatches in two-step-processed (TSP) p-i-n PSCs, boosting PCE to 25.6%. 2 Sn(OTF)2 enhances NiOx conductivity, suppresses ion migration, and forms a Pb-Sn perovskite interlayer; F-PEA eliminates PbI2, forming a 2D capping layer for defect passivation. 3 Optimized NiOx-based TSP p-i-n PSCs retain 84% initial power conversion efficiency after 720-h light illumination, providing design principles for 26%-efficiency devices.